A casebook of cognitive therapy for traumatic stress reactions - Grey, Nick, 1970- (Routledge, 2009)
A Casebook of Cognitive Therapy for Traumatic Stress Reactions aims to help therapists who may lack specific training or who may not have an extensive range of clinical experience.